Feather-Work: A Fashioned Ostrich Plume Embodies Hybrid and Violent Labors of Growing and Making. Issue 1 (1st June 2021) - Patchett, Merle
Abstract : This paper uses a fashioned ostrich plume to conceptualize and re-present ostrich "feather-work" as being co-constituted by human and non-human labor. The plume archives not only the human hands that fashioned it but also the bird-body that grew the feathers, insisting it be conceptualized and researched as a grown-made commodity. From this starting point, I reconstruct its journey along the "feather-road": from reared and plucked ostrich on a South African ostrich farm to willowed plume in Euro-American sweatshops. By fleshing-out the "hybrid labor" involved in the plume's growing and making, I demonstrate that feather-work not only exploited indigenous African, indentured migrant, and sweated immigrant human laborers, but how it yoked the reproductive and metabolic labor of ostriches. By doing so the paper illustrates how this luxury feather-fashion accessory is historically implicated in colonial, economic, and ecological violence, locating the troubling journeys of fashion's "bio-commodities" further back in time.